2022
DOI: 10.3389/fpls.2022.897843
|View full text |Cite|
|
Sign up to set email alerts
|

Organization, Phylogenetic Marker Exploitation, and Gene Evolution in the Plastome of Thalictrum (Ranunculaceae)

Abstract: Thalictrum is a phylogenetically and economically important genus in the family Ranunculaceae, but is also regarded as one of the most challengingly difficult in plants for resolving the taxonomical and phylogenetical relationships of constituent taxa within this genus. Here, we sequenced the complete plastid genomes of two Thalictrum species using Illumina sequencing technology via de novo assembly. The two Thalictrum plastomes exhibited circular and typical quadripartite structure that was rather conserved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…In this study, a total of 1968 SSRs were identified in the plastomes of 79 Trichosporeae species, with 89.99% of them being mono-nucleotide repeats ( Figure 4 ; Table S4 ). These results are consistent with previous studies of other angiosperms ( Xiang et al., 2022 ; Yu et al., 2022 ). Plastome SSRs usually consist of short polyA or polyT repeats and mono-nucleotide repeats ( Provan et al., 2001 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, a total of 1968 SSRs were identified in the plastomes of 79 Trichosporeae species, with 89.99% of them being mono-nucleotide repeats ( Figure 4 ; Table S4 ). These results are consistent with previous studies of other angiosperms ( Xiang et al., 2022 ; Yu et al., 2022 ). Plastome SSRs usually consist of short polyA or polyT repeats and mono-nucleotide repeats ( Provan et al., 2001 ).…”
Section: Discussionsupporting
confidence: 94%
“…Plastome SSRs usually consist of short polyA or polyT repeats and mono-nucleotide repeats ( Provan et al., 2001 ). The variation in the non-coding region was higher than that in the coding region, with the variation in the SC region being higher than that in the IR region, which is like other angiosperms plastomes ( Xiang et al., 2022 ). Five hypervariable CDSs ( rps15 , matK , ndhF , rps16 and rpl32 ) and eight hypervariable non-coding regions ( rpl16/rps3 , rpl14/rpl16 , petB/petD , trnC-GCA/petN , rps15/ycf1 , trnfM-CAU/rps14 , petD/rpoA and trnS-GGA/rps4 ) were identified in Trichosporeae ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies on other angiosperm groups have shown that chloroplast genomes are conserved or highly polymorphic ( Abdullah et al., 2020 , Abdullah et al., 2021 ). In the present study, the cp genome was highly conserved in terms of gene order, gene content, and intron number, following the findings of many other taxa, including Thalictrum ( Tang et al., 2015 ; Yu et al., 2018 ; Xiang et al., 2022 ). However, in some taxa, such as Amorphophallus of Araceae, some genes were lost ( Liu et al., 2019 ), and in others, such as Pelargonium ( Chumley et al., 2006 ), the structure and gene order diverged from those reported here and in most other angiosperms.…”
Section: Discussionsupporting
confidence: 80%
“…The plastome of this species varies in terms of genomic structure, nucleotide diversity, structural alterations, and phylogeny with the plastomes of Thalictrum species ( Park et al., 2015 ; He et al., 2019 ; Morales-Briones et al., 2019 ; He et al., 2021 ; Cai et al., 2022 ; Zhe et al., 2023 ). For instance, there is an apparent difference between Thalictrum plastomes in the IR-SC boundary areas, which causes variations in genome size ( Xiang et al., 2022 ). IR-SC contractions or expansions into or out of neighboring single-copy regions are typically observed in angiosperm plastomes, and this process is a primary mechanism and an example of length variation in cp genomes ( Kim and Lee, 2004 ; Yang et al., 2016 ; Zhang et al., 2016 ; Ye et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation